Synthesis of building blocks for two-dimensional supramolecular assembly by hydrogen bonding between melamine and imide functionalities - Chng, Grace Yan Yan. (2011)
Organic based materials forming supramolecular assembly have generated significant interest in many areas, such as electronics, optoelectronics, photonics, and energy storage. Self-assembly by hydrogen bonding provides a mechanism for assembling large numbers of molecules into stable structures which lead to synergistic and emergent properties that are not intrinsic to the building blocks themselves. The concepts of supramolecular organization have been applied to two-dimensional assemblies on surfaces stabilized by hydrogen bonding. The molecular engineering concept involves multivalent molecular modules that are programmed to undergo heteromolecular recognition by its complementary multiple hydrogen bonds. Two types of molecular modules have been engineered: (i) melamine derivatives (ii) imides structures. These molecular modules self-assemble through hydrogen bonds between the complementary recognition sites, forming supramolecular architectures. Their symmetry depends upon the type of each individual subunit and the stoichiometry as well as on the combination and distribution of the main symmetry axes. In this project, melamine derivatives and imides are synthesized and tested for their self-assembled supramolecular structure via UV-visible absorption and emission titration, and atomic force microscopy (AFM).